2014
DOI: 10.1017/s2045796014000110
|View full text |Cite
|
Sign up to set email alerts
|

Risk of post-traumatic stress disorder following traumatic events in a community sample

Abstract: Nearly one-half of a general community sample had experienced a traumatic event and of these around one in seven was a DSM-IV case of PTSD. Although the majority of research has concentrated on combat, rape and assaultive violence, life threatening illness is a more common cause of PTSD in the community. Removal of this traumatic event in DSM-5 could reduce the number of cases of PTSD by around 6.0%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 29 publications
1
29
1
Order By: Relevance
“…68,2931 Our findings of lower-than-mean ORs among civilians in a war zone or a region of terror and those who experience natural disaster, in comparison, are perplexing given the results regarding atrocities and numerous focused studies of high levels of PTSD after disasters. 32,33 However, further investigation provides plausible explanations.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…68,2931 Our findings of lower-than-mean ORs among civilians in a war zone or a region of terror and those who experience natural disaster, in comparison, are perplexing given the results regarding atrocities and numerous focused studies of high levels of PTSD after disasters. 32,33 However, further investigation provides plausible explanations.…”
Section: Discussionmentioning
confidence: 94%
“…68 This failure occurred because the pattern applied only to repeated exposures, which were controlled for in our models. For sexual violence, in comparison, we found that prior exposure was not relevant.…”
Section: Discussionmentioning
confidence: 99%
“…However, they can result in almost identical symptoms and raise questions about the validity of the definitions for traumatic events. 18 …”
Section: How Is Ptsd Diagnosed?mentioning
confidence: 99%
“…Epidemiological data have consistently shown that only a minority of those suffering from mental disorders receive basic evidence-based treatments, and relatively few people with mental disorders consult a physician (Tol et al 2013). In developing countries, health systems often are not able to provide even the most essential mental care, including essential medicines for mental disorders (White et al 2014). Strategies aimed at improving access and rational use of psychotropic medicines should therefore receive more attention, with particular emphasis on the following topics (World Health Organization, 2005):…”
mentioning
confidence: 99%